Efforts to enhance the achievement motivation of amputee football athletes using the goal-setting module - Eka Kurnia Darisman; Mulyono Mulyono; Moh Hanafi; Gatot Margisal Utomo; Agatha Candrika; Wahyu Indar Pramuji; Salsabila Maghfira (Sriwijaya Journal of Sport, 2025)
Research Problems: Goal setting is a psychological technique designed to help individuals establish specific, measurable, attainable, relevant, and time-bound (SMART) goals. Research Objectives: Implementing the goal-setting module for athletes with special needs is expected to enhance their focus, discipline, and drive to excel. Methods: This study employs an experimental design. In this design, a group of athletes is given treatment by using a goal-setting module. The population and sample of this study consist of 12 special needs football athletes from the PERSAS (Persatuan Sepakbola Amputasi Surabaya) club. Results: Overall, the athletes’ ability to set short-term goals showed a positive response. By the end of the period, 6 athletes (50%) were able to set more than five short-term goals, 3 athletes (25%) set 3-4 goals, 2 athletes (16%) set two goals, and 1 athlete (9%) managed to set only one short-term goal. The data indicate that athletes with more experience in terms of achievements and age tend to have a greater ability to determine multiple goals they wish to achieve. Conclusion: This study concludes that guiding the goal-setting process significantly improves the ego and task orientation, as well as the goal-setting strategies, of PERSAS Surabaya amputee football athletes. This ability to set goals positively impacts their persistence, motivation, and self-confidence.